Impact of gonadectomy on blood pressure regulation in ageing male and female rats - Pijacka, Wioletta; Clifford, Bethan; Walas, Dawid; Tilburgs, Chantal; Joles, Jaap A.; McMullen, Sarah; Langley-Evans, Simon C. (BioMed Central, 2016)
Sexual dimorphism in blood pressure has been associated with differential expression of the angiotensin II (AII) receptors and with activity of the nervous system. It is generally accepted that aging affects kidney function as well as autonomic nervous system and hormonal balance. Given that hypertension is more prevalent in men than women until women reach their seventh decade we hypothesised that females would be relatively protected from adverse effects of ageing compared to males, and that this would be mediated by the protective effect of ovarian steroids. Intact and gonadectomised male and female normotensive Wistar rats aged 6, 12 and 18 months were used to study renal function, blood pressure, heart rate and blood pressure variability. We observed that intact females had lower levels of proteinuria and higher (12.5%) creatinine clearance compared to intact males, and that this difference was abolished by castration but not by ovariectomy. Ovariectomy resulted in a change by 9% in heart rate, resulting in similar cardiovascular parameters to those observed in males or gonadectomised males. Spectral analysis of systolic blood pressure revealed that high frequency power spectra were significantly elevated in the females vs. males and were reduced by ovariectomy. Taken altogether the results show that females are protected from age-related declining renal function and to a lesser extent from rising blood pressure in comparison to males. Whilst ovariectomy had some deleterious effects in females, the strongest effects were associated with gonadectomy in males, suggesting a damaging effect of male hormones.